Analysis of Health Workers Factors on The Success of Early Breastfeeding Initiation at Hospital - Kusumaningrum, Hesti; Khana, Fitri Hijri (JOURNAL EDUCATIONAL OF NURSING(JEN), 2022)
According to WHO, there was a decrease in the rate of exclusive breastfeeding to 67.96% compared to 2021, which was 69.7%, through efforts to provide breast milk as early as possible by carrying out EBF. Early Breastfeeding Initiation (EBF) is the process of skin-to-skin contact between the baby and the mother immediately after the baby is born for at least one hour. EBF initiates the success of mothers and newborns to continue the breastfeeding process with Exclusive Breastfeeding. The proportion of exclusive breastfeeding is 44% greater in mothers who do EBF. The support of health workers is critical in the implementation of EBF. The purpose of the study was to analyze health worker factors in the implementation of EBF in health facilities. The research method was quantitative-observational with a cross-sectional approach. Results: The number of samples based on Accidental Sampling was 45 health workers who were on duty in the delivery room within a period of 1 month. Health workers who implemented EBF according to procedure were 15 people (34.3%) and 30 people who implemented EBF but not according to procedure (66.7%). There was a relationship between knowledge (p = 0.004), attitude (0.000), support from colleagues (p = 0.016), and access to information for health workers with the implementation of EBF according to the procedure. Suggestion: Every healthcare staff needs to refresh every health worker about the correct EBF implementation procedure to improve the competence of health workers in facilitating the implementation of EBF during childbirth in health facilities.